Tuning the aroma profiles of FORASTERO cocoa liquors by varying pod storage and bean roasting temperature. (November 2019) - Hinneh, Michael; Van de Walle, Davy; Tzompa-Sosa, Daylan Amelia; De Winne, Ann; Termote, Sarah; Messens, Kathy; Van Durme, Jim; Afoakwa, Emmanuel Ohene; De Cooman, Luc; Dewettinck, Koen
Abstract: The unique impact of roasting conditions on the aroma quality of cocoa beans has been demonstrated in many studies. However, information on the additional impact of pod storage (PS) and its combined effect with roasting temperature (RT) is unknown. Hence, this study sought to elucidate the collective contribution of these post-harvest/process parameters on the aroma profiles of cocoa liquors produced from Forastero cocoa beans. The beans had been subjected to different treatments following a 3 × 4 full factorial experiment, consisting of PS (0, 3, 7 days) and RT (100, 120, 140, 160 °C). Statistical analysis of the results from HS-SPME-GC–MS revealed significant ( p < .05) impact of both PS and RT as well as their interaction effects on the ten groups of volatiles (acids, alcohols, esters, terpenes, aldehydes, ketones, pyrazines, furans, pyrroles and others) and their overall aroma concentration. An exception was however noted for aldehydes, where the total concentration was only significantly ( p < .05) influenced by the individual effects of PS and RT. A subsequent clustering of the liquors, first on the basis of all identified volatiles, then, on the basis of the odor-active volatiles, also revealed similar pattern where liquors with high RT's possessed more volatiles with higher concentrations and vice versa . More so, it seemed that no or very minimal PS treatment was necessary for preserving more aromatic volatiles with typically fruity, floral or spicy flavor notes, whereas, for liquors with volatiles exhibiting more cocoa, chocolate, nutty and roasted flavor notes, prolonged PS (> 3 days) treatment was required. These findings are expected to challenge the status-quo, specifically in the conventional ways through which the aroma potential of 'bulk' cocoa may be steered. On the one hand, the idea of manipulating PS treatment and roasting conditions may indeed consolidate the possibility of creating diverse and/or distinct aroma profiles from the same 'bulk' cocoa beans, whereas, on the other hand, it raises the question whether the Ghanaian cocoa beans - being described as 'bulk' cocoa - could be a consequence of prolonged pod storage treatment. Graphical abstract: Unlabelled Image Highlights: Significant interaction effect of PS and RT on all groups of aroma volatiles, except for aldehydes. At all PS treatments, high roasting intensities yielded more aroma volatiles except for aldehydes and ketones. No or very minimal PS treatment was necessary for preserving more volatiles with fruity and floral notes. Prolonged PS treatment yielded liquors with volatiles exhibiting more cocoa, chocolate, nutty and roasted flavor notes.